REFLECTING ON ANALOGUE FACES AND DIGITAL MASKS THROUGH MISSION: IMPOSSIBLE (1996-2023) - Chris Broodryk (Persona Studies, 2024)
This article uses the idea and practice of the mask and masking technology in the popular Mission: Impossible film franchise to critically consider the tensions between digital and analogue. In the Mission: Impossible films, the masks are a core component of the films’ intrigue, and they serve the plot dynamics of each franchise entry while also revealing ever-sophisticated diegetic film technologies that make these silicone-based masks increasingly hyper-realistic in spy-craft and anti-surveillance deception. This article demonstrates how the mask is an identity technology that qualifies the persona as potentially deceptive and duplicitous as it relies on a convincing presentation of a character’s self that does not accurately reflect the interiority of this character, and on a betrayal of trust of the affective investment of a particular micro-publics. As such, the viewer reflects on facial representation not only in terms of verisimilitude, but also veracity. Within a context of techno est ubique, the mask has evident transformative capacities as a temporary interface with the world and as a remediation technology. However, the mask is also a precarious technology because it is highly visible and needs monitoring for proper presentation and error. It is a seamless technology, which evokes further reflections on photorealism and deepfakes. Additionally, digital comes to denote ‘dead’, and the digital mask of especially the later Mission: Impossible films – identifiable by its skeuomorphic qualities – challenges the continued existence of the analogue (organic face) as mask and related appearance replication technologies come to replace human faces and bodies entirely.